Modelling and implementation of complex systems : proceedings of the 5th International Symposium, MISC 2018, December 16-18, 2018, Laghouat, Algeria /: proceedings of the 5th International Symposium, MISC 2018, December 16-18, 2018, Laghouat, Algeria. ([2019]) - Unknown
No abstract available